2008
DOI: 10.1038/nrc2393
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dysfunction and tumour suppression: the senescence connection

Abstract: Long lived organisms such as humans have evolved several intrinsic tumor suppressor mechanisms to combat the slew of oncogenic somatic mutations that constantly arise in proliferating stem cell compartments. One of these anti-cancer barriers is the telomere, a specialized nucleoprotein that caps the ends of eukaryotic chromosome. Impaired telomere function activates the canonical DNA damage response pathway that engages p53 to initiate apoptosis or replicative senescence. Here, we discuss how p53-dependent sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
287
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(295 citation statements)
references
References 98 publications
4
287
0
4
Order By: Relevance
“…2 B and C). To determine whether elevated GAPDH gene expression might potentially alter the gene expression of hTERT, the catalytic subunit and rate-limiting component of telomerase (32,33), we measured hTERT gene expression by real-time PCR and found that there were no significant changes in the hTERT gene expression levels (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…2 B and C). To determine whether elevated GAPDH gene expression might potentially alter the gene expression of hTERT, the catalytic subunit and rate-limiting component of telomerase (32,33), we measured hTERT gene expression by real-time PCR and found that there were no significant changes in the hTERT gene expression levels (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…This type of senescence, termed replicative senescence, is caused by the shortening of a telomere, which is a protective structure capping the end of eukaryotic chromosomes [2].…”
Section: Introductionmentioning
confidence: 99%
“…10 The accumulation of such shortening results in loss of telomeric DNA and, eventually, los of chromosome capping, which triggers p53-mediated senescence and/or apoptosis, thus limiting lifespan at the cellular level. 11 Telomere shortening is counteracted by telomerase activity. This ribonucleoprotein complex is composed of two main subunits: the telomerase reverse transcriptase (TERT, encoded by TERT; GeneEntrez ID: 7015), which promotes telomere elongation by reverse transcription, and the telomerase AdvAnces in Tumor virology 2014: 4 RNA component (TERC, encoded by TERC; GeneEntrez ID: 7012), which serves as a template for the reaction.…”
Section: Telomeres and Telomerase In Aging And Cancer: An Overviewmentioning
confidence: 99%